The Moisture Content of Sawdust Fuel Pellets at Different Drying Periods - Junaidi Junaidi; Yustina Metanoia Pusparizkita; Attaya Juliatiko; Ngakan Ade Rahmadiputra; Sudarno Sudarno (Universitas Diponegoro, 2022)
The development of pellet fuel from biomass has a great opportunity because Indonesia is an agricultural country. Utilizing this biomass can increase economic value, minimize waste generated, and reduce emissions released into the environment. In this study, the pellet fuel was made from sawdust obtained from the Semarang wood sawmill industry. The raw materials are mixed with adhesive, water and then formed using a pellet machine. The high water content in the pellets that have just come out of the pelletizing (27%) process requires drying treatment. The aim of this work was to find out the effect of drying time on the moisture content of the pellet fuel to meet existing standards. The variation of drying time used is 10, 15 and 20 minutes at 100° C. The results showed that the moisture content of the pellet was 22% (10 min), 19% (15 min) and 17% (20 min). The water content in the pellets will decrease 4% on average along with the drying time. However, the water content was still slightly higher than the specified standard (8-13%). Based on model predictions, the necessary drying time is 30-35 min. Ash content obtained from this study is 0.7%. The drying time can affect the density of the resulting pellet product. Accordingly, further studies are needed to determine the drying optimum temperature.